1990
DOI: 10.1016/0014-4835(90)90142-h
|View full text |Cite
|
Sign up to set email alerts
|

The filtration characteristics of the aqueous outflow system

Abstract: To determine the filtration characteristics of the aqueous outflow system, microspheres (0.18 pm-l.1 pm) were perfused through enucleated human and bovine eyes. The microspheres were smaller than morphologically determined flow dimensions, and yet a significant fraction of all sizes of microspheres were captured. The bovine (calf) aqueous outflow system was found to be a far more efficient filter than was the human outflow system.Combining the experimental results with morphological observations and theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…It was found in these studies that a filtration barrier existed for particles larger than roughly one half micrometer or so, and thus it was concluded that pores nearly one micrometer in size must exist. More recent studies have confirmed this conclusion using microparticles and latex microspheres (Huggert, 1955;Huggert et al, 1955;Karg et al, 1959;Johnson et al, 1990). …”
Section: The Inner Wall Endothelium Of Schlemm's Canalsupporting
confidence: 59%
See 1 more Smart Citation
“…It was found in these studies that a filtration barrier existed for particles larger than roughly one half micrometer or so, and thus it was concluded that pores nearly one micrometer in size must exist. More recent studies have confirmed this conclusion using microparticles and latex microspheres (Huggert, 1955;Huggert et al, 1955;Karg et al, 1959;Johnson et al, 1990). …”
Section: The Inner Wall Endothelium Of Schlemm's Canalsupporting
confidence: 59%
“…Nor has any alternate explanation been offered for the relatively easy passage of microparticles 200-500 nm in diameter through the outflow pathway (Johnson et al, 1990), except through these large pores. Since there are intact tight junctions between the inner wall cells (presumably to prevent blood reflux into the eye that can occur during periods of transient increases in ocular venous pressure), there are no other structures apparent in this endothelium that could explain the high hydraulic conductivity of this tissue or its filtration characteristics.…”
Section: The Inner Wall Endothelium Of Schlemm's Canalmentioning
confidence: 99%
“…Studies utilizing tracer particles including zymosan, latex microspheres, cationic ferritin, and fluorescent Qdots indicated that segmental variations in outflow exist. (Battista et al, 2008; Buller et al, 1990; de Kater et al, 1989; Ethier and Chan, 2001; Hann et al, 2005; Hann and Fautsch, 2009; Johnson et al, 1990; Keller et al, 2011; Lu et al, 2008; Lu et al, 2011) The TM can therefore be separated into regions of high and low outflow, which appears to be consistent across species (human, monkeys, bovine, mice). Logically, there must be molecular differences between the components of each region that either affect or reflect the geographical outflow pathways.…”
Section: Function Of the Tmmentioning
confidence: 94%
“…[36][37][38] More recently, microspheres of 0.18 m and 1.1 m diameter, perfused at concentrations of 3-5 × 10 5 and 3 × 10 3 per ml, were thought to be captured in the filtration system because of sticking to the tissue and not as a function of size. 39 In that study, no measurements of outflow facility were conducted. Here, we have used a particle that is smaller (90 nm diameter), in about 1000 × higher concentration (10 8 p.f.u.…”
Section: Adenoviral Particles (Arrows) Appear In Close Association Wimentioning
confidence: 97%